Biomechanical effects of postural and cognitive loads on trunk of workers performing assembly tasks at hand functional height - Huishuan WU; Yu JIN; Yan LIU; Siyi ZENG; Cunwen QIAN; Kezhi JIN (环境与职业医学)
BackgroundThe neck, shoulders, and lower back are the primary affected areas of work-related musculoskeletal disorders. In manual tasks, combinations of hand functional height (defined as working height below the waist), awkward postures, and cognitive load are common risk factors. However, there is limited literature documenting how these factors specifically alter biomechanical load on the neck, shoulders, and lower back when working at hand functional height.ObjectiveTo explore quantitative differences in biomechanical load on the neck, shoulders, and lower back of workers performing manual tasks at hand functional height under different postures and cognitive load combinations. MethodsA 3x2 within-subject design was implemented, with three postures (squat, kneeling, and stoop) and two levels of cognitive load (with cognitive load induced by a 2back task and without cognitive load). Ten male university students were recruited to perform a predetermined assembly task (a sequence of loosening and tightening screws) at hand functional height. Surface electromyography (sEMG) and 3D motion capture system were employed to assess the participants’ trunk biomechanical load in executing the tasks. Additionally, subjective perception, including fatigue, muscle pain, and cognitive load, were evaluated using scales.ResultsSignificant variations in biomechanical load were observed across the three postures (P<0.05). The stoop posture exhibited the lowest muscle activation in most target muscles, except for the sternocleidomastoid, and showed the fastest decline in instantaneous median frequency (IMF) of the erector spinae, with a rate of (-0.050±0.008) Hz per unit time (0.128 s), and the greatest trunk flexion angle (35.14°±4.40°). Performing the task by squatting resulted in the highest muscle activation, especially in the upper trapezius, where maximum voluntary contraction percentage reached 20.07%±1.26%. In addition, the squatting posture also resulted in larger joint angles in the sagittal plane for the neck (−7.03°±2.70°), shoulders (60.20°±7.89°), and lower back (34.42°±4.20°). The kneeling posture showed intermediate muscle activation, the slowest IMF decline for the erector spinae in the lower back (−0.005±0.008) Hz per unit time (0.128s), and the joint angles were closest to neutral. The task performance results were also superior in the kneeling posture. Regarding cognitive load, no significant differences were found for most biomechanical indicators, except for subjective cognitive load scores, neck flexion, and shoulder external rotation angles.ConclusionIn assembly tasks performed at hand functional height, kneeling results in moderate biomechanical load on the neck, shoulders, and lower back while also improves task performance compared to squatting and forward bending. Additionally, no significant effects of cognitive load under the 2back condition on biomechanical load are observed.